Аналітичний інструментарій оцінки рівня фінансового розвитку підприємства за умов реалізації мотиваціно-орієнтованого управління - Антипцева, О. Ю. (НТУ "ХПІ", 2014)
Визначено, що для сучасного економічного становища України збереження переважно сировинного напрямку господарської діяльності має високий рівень економічної небезпеки. Доведено - перспективною організаційною формою підприємства, спроможного забезпечити інноваційний розвиток, конкурентоспроможність на світових ринках і зміцнення економічної безпеки України, є українська корпорація.

The article examines approaches to assess the level of financial development company and the level of implementation of motivational-oriented management of financial development. A comparative analysis of assessment methods. It is proved that in the emerging knowledge economy for managerial staff enterprises are finding out not only of motivational possibilities of organizational and managerial staff but also study the likely impact of motivational factors on the results of its financial development, which is possible due to the implementation of integrated assessment methods . Grounded inclusion complex methods of analytical tools to assess the level of financial development enterprises in the implementation of motivational-oriented management. Analytical tools allows to investigate patterns of changes in the effective rate of financial enterprises in the consideration of motivation-oriented control, depending on changes in the values of various factors (consolidated using the integral index motivational components.
Analytical tools assess the level of financial development enterprises in the implementation motivational-oriented management
Keywords: підприємство; економічна безпека держави; "сировинна" економіка; корпорація; business; financial development; motivational factors; motivational-oriented management; analytical tools; evaluation methods; integral method of evaluation